Ineffective Strategies in Scientific Communication: Textual Wordiness vs. Clarity of Thought in Thesis Conclusion Section - Elena V. Tikhonova; Marina A. Kosycheva; Daria A. Mezentseva (National Research Mordova State University, 2024)
Introduction. The issue of lexical redundancy in academic writing remains crucial. Research based on Russian-language corpora is vital for the development of effective targeted academic writing courses that meet the unique needs of universities. This paper aims to identify factors through examples of wordiness in the Conclusion sections of theses to alter the design of courses broadening academic writing skills to fight against textual redundancy at various educational levels. Materials and Methods. A corpus of 72 theses across three educational levels (Bachelor's, Master's, and Candidate degrees) was analyzed. We selected theses from the repositories of the HSE University and Moscow City University. We focused on Conclusion section due to its highest level of conciseness: textual redundancy critically impacts its effectiveness. The analysis included a comprehensive procedure of raw data extraction, coding, conceptualization during iterative discussions, and classification according to Brohaugh's taxonomy. Results. "Invisible" type of wordiness is a prevalent issue in academic writing across all levels of education. Such types as "overkill", "weak-kneed" and "empty" occur more frequently in research in Master's and Candidate's theses. The need to comprehend the reasons behind the use of different types of wordiness and their impact on readability is stressed. Candidate's theses are wordier despite the expectation of a higher level of academic writing skills at this level. Discussion and Conclusion. The study highlights the systemic role of academic writing courses at all educational levels in reducing text wordiness. Despite our expectations of advanced writing skills in Candidate's theses, their high level of wordiness indicates the need for developing effective academic writing strategies. It is crucial to implement a personalized approach to academic writing instruction, considering the specific needs and challenges of each educational level, to create more concise academic texts. The paper provides insights into approaches to designing academic writing courses.